Study of Structural Defects Evolution in Fine-Grained Concrete Using Computed Tomography Methods - A. V. Puzatova; M. A. Dmitrieva; A. О. Tovpinets; V. N. Leitsin (Advanced Engineering Research, 2024)
Introduction. When studying composite materials for construction purposes, it is needed to consider the mechanisms of formation of the structure and properties of modern concretes in the process of strength development. In studies of modern composite materials based on cement binder, there is no information about the development of structural defects and destruction of the material at the initial stages of strength development. This information can be obtained using X-ray computed tomography, a promising method of nondestructive testing of the state of the material. Therefore, the objective of this work was to study the formation and propagation of cracks in samples of fine-grained concrete with different fractional composition of sand due to natural processes of cement shrinkage, as well as the mechanics of destruction of samples of modified fine-grained concrete when applying a compressive load at the early stages of strength development. Materials and Methods. The study used fine-grained concrete mixtures of three compositions with different sand gradation. The tomography samples were made by placing fresh mixtures in polymer cylindrical containers. Tomography of the samples immediately after manufacture, as well as after 8 and 51 days, was performed in a YXLON Cheetah microfocus X-ray machine. The composition with two-fraction sand was modified by mechanical activation of the components, 20×20×20 mm cube samples were made. Further, compression tests were performed at the Instron installation after 3 and 7.5 hours, and then — tomography of the destroyed samples.Results. It was established that the destruction of contact zones depended on the ratio of the size of the fractions. In the presence of a bulk of coarse sand grains in concrete, the destruction of contact zones was more pronounced and had a main mode. When using fine or polyfraction sand, contact zones were destroyed locally and had a visually smaller area. The images of the destroyed modified sample, tested 3 hours after manufacturing, showed clear cracks and indents on the edges, which indicated the elastic-plastic nature of the destruction. In 7.5 hours, the edges of the sample upon destruction were covered with a network of small cracks; inside the sample there were also numerous cracks and microcracks, which indicated brittle fracture. Based on the obtained images of the deformed structure of modified concrete, the mechanism of transition from elastic-plastic destruction of the material to brittle one was clearly visible.Discussion and Conclusion. The studied dependences of the influence of the size of fine aggregate on the mechanisms of formation and propagation of structural defects contribute to the theory of the processes of destruction of fine-grained concretes. The results obtained prove the prospects of using X-ray computed tomography as a method of nondestructive testing of the internal structure of fine-grained concrete, including at the early stages of strength development.